2010
DOI: 10.1111/j.1478-3231.2009.02136.x
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic steatohepatitis induces non-fibrosis-related portal hypertension associated with splanchnic vasodilation and signs of a hyperdynamic circulationin vitroandin vivoin a rat model

Abstract: Steatohepatitis induces significant portal hypertension (PHT) in the absence of fibrosis, associated with an increase in mesenteric arterial and portal venous flow, arterial hyporesponsiveness to vasoconstrictors and a decrease in MABP, indicating the presence of splanchnic vasodilation and hyperdynamic circulation. These alterations resemble those seen in cirrhotic PHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
54
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 38 publications
9
54
1
Order By: Relevance
“…10 In the present series we confirm the presence of PHT in patients with NAFLD, in the absence of significant fibrosis, confirming our experimental findings. As some patients were taking antihypertensive drugs, the results might even underestimate the problem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…10 In the present series we confirm the presence of PHT in patients with NAFLD, in the absence of significant fibrosis, confirming our experimental findings. As some patients were taking antihypertensive drugs, the results might even underestimate the problem.…”
Section: Discussionsupporting
confidence: 91%
“…This rise in portal pressure is associated with systemic vascular hyporeactivity, increased splanchnic blood flow and signs of a hyperdynamic circulation. 10 These features resemble the hemodynamic changes that are well documented in cirrhotic PHT. 11,12 We subsequently examined the hepatic venous pressure gradient (HVPG) in a prospectively included series of patients with overweight and hence a risk of NAFLD.…”
Section: Introductionsupporting
confidence: 52%
“…We also showed that this increase in portal pressure was related to the severity of the steatosis and occurred in the complete absence of fibrosis. Furthermore, we showed that the increase in portal pressure coincides with the development of severe steatosis and precedes necro-inflammatory changes, 10 leading to the hypothesis that steatosis-related increase in intrahepatic resistance might, via local ischaemia, contribute to the progression of NAFLD to NASH. These findings appeared to be clinically relevant, as we could demonstrate portal hypertension in a group of obese NAFLD patients with severe steatosis but minor degrees of fibrosis.…”
mentioning
confidence: 77%
“…12 We previously demonstrated in a detailed analysis of our model that the MCD diet in our male Wistar rats rapidly induces steatosis, which is already almost 100% at week 3, whereas signs of inflammation and oxidative stress develop only beyond 4 weeks of MCD diet. 10 The protocols were approved by the Antwerp University Ethical Committee on Animal Experiments, and the animals received human care and were treated according to the Helsinki declaration, the national guidelines for animal protection and the 'Guide for the Care and Use of Laboratory Animals' (National Institutes of Health, 1985).…”
Section: Materials and Methods Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation